Quality of life and experiences of sarcoma trajectories (the QUEST study): protocol for an international observational cohort study on diagnostic pathways of sarcoma patients - Vicky Soomers; Olga Husson; Ingrid ME Desar; Lonneke V van de Poll-Franse; Winette TA van der Graaf (BMJ Open)
Introduction Sarcomas are rare tumours with considerable heterogeneity. Early and accurate diagnosis is important to optimise patient outcomes in terms of local disease control, overall survival (OS) and health-related quality of life (HRQoL). Time to diagnosis is variable in bone as well as soft tissue sarcoma. Possible factors for a long time from first symptom to diagnosis (the total interval) include patient, tumour and healthcare characteristics, but until now the most relevant risk factors and its association with outcomes remain unknown. Our study aims to (1) quantify total interval, the time interval from first symptom until (histological) diagnosis; (2) identify factors associated with interval length and (3) determine the association between total interval and HRQoL, stage and tumour size at diagnosis, progression-free survival (PFS) and OS.Methods and analysis We will conduct a longitudinal, prospective, international, multicentre cohort study among patients aged ≥18 years with newly diagnosed bone or soft tissue sarcoma at eight centres (three in UK, five in The Netherlands). Patients will be asked to complete questionnaires at five points in time; one at diagnosis and at follow-up points of 3, 6, 12 and 24 months. Questionnaire data is collected within the Patient Reported Outcomes Following Initial treatment and Long term Evaluation of Survivorship (PROFILES) registry: an international data management system for collection of patient-reported outcomes. Clinical data will be extracted from patient records. The primary endpoint is HRQoL at diagnosis, measured with the EORTC QLQ-C30. Secondary endpoints are stage and tumour size at diagnosis, PFS, OS, additional patient-reported outcomes, such as quality-adjusted life years and psychological distress.Ethics and dissemination Ethical approval was given by the Health Research Authority and Research Ethics Committee for the United Kingdom (18/WA/0096) and medical ethical committee of Radboudumc for The Netherlands (2017-3881). Results will be presented in peer-reviewed journals and presented at meetings.Trial registration number NCT03441906.